Destructive intergenerational altruism - Geir B. Asheim; Frikk Nesje (University of Oslo, Department of Economics, 2015)
Are the probable future negative effects of climate change an argument for decreasing the discount rate to promote the interests of future generations? The analysis of the present paper suggests that such stronger intergenerational altruism might undermine future wellbeing if not complemented by collective climate action. In the standard one-sector model of economic growth normatively attractive outcomes will be implemented if each generation has sufficient altruism for its descendants. This conclusion is radically changed in a two-sector model where one form of capital is more productive than the other, but leads to negative atmospheric externalities. In fact, the model shows that, if each dynasty is trying to get ahead in a world threatened by climate change by increasing its intergenerational altruism, then long-term wellbeing will be seriously undermined.
Keywords: D63; D64; D71; Q01; Q54; 330; intergenerational altruism; climate change